Pyrostria triflora, a new species of Vanguerieae (Rubiaceae) from Luzon, Philippines - Arriola, A.H.; Camacho, P.D.; Calaramo, M.J.A.; Alejandro, G.J.D. (Bangladesh Journal of Plant Taxonomy, 2015)
Pyrostria triflora, a new species of the tribe Vanguerieae of Rubiaceae from the Philippines is described and illustrated. The new species is unique from other representatives of the genus by its strictly 3-flowered inflorescences and geographic distribution. Bangladesh J. Plant Taxon. 22(1): 5558, 2015 (June)